Checkpoint Inhibitors in Cancer Immunotherapy: Mechanisms of Action and Resistance - Ghadah Ali Al-Oudah; Wallaa Luay Alfalluji; Ahmed M N Al-Ajrash (Journal of Biomedicine and Biochemistry, 2025)
Immune checkpoint inhibitors have revolutionized the treatment landscape for various malignancies by enhancing the body’s natural immune response against tumor cells. Targeting molecules such as CTLA-4 and PD-1/PD-L1, these therapies release the brakes on T-cell activation and proliferation. Despite impressive clinical outcomes in melanoma, lung cancer, and renal carcinoma, a significant proportion of patients exhibit primary or acquired resistance. This review delves into the molecular mechanisms of checkpoint blockade, discusses biomarkers predictive of response, and explores resistance pathways including immunoediting, tumor microenvironment immunosuppression, and upregulation of alternative checkpoints. Novel strategies to overcome resistance, such as combination therapies and personalized immunotherapeutics, are critically analyzed.